Effect of diode laser irradiation and 10% citric acid conditioning on the sealing ability of mineral trioxide aggregate as a retrograde filling material - Shailendra Mashalkar; Syed Mubeen Mohiuddin Hussaini; Pavan Diwanji; Shreeshail Indi; Ashwini Hambire (Wolters Kluwer Medknow Publications, 2020)
Aim: The aim was to evaluate the effect of diode laser irradiation and 5% citric acid conditioning on microleakage of mineral trioxide aggregate (MTA) when used as root-end filling material. Materials and Methods: Forty-five human anterior teeth were decoronated and subjected to root canal instrumentation. Three millimeters of apical root portion was resected, and root-end cavities were prepared using ultrasonic tips. The teeth were then randomly divided into three groups (n = 15), In Group 1 - root-end cavity was prepared and treated with citric acid followed by MTA application; in Group 2 - root-end cavity was prepared and treated with diode laser followed by MTA application; and in Group 3 - root-end cavity was prepared and treated with citric acid and laser application followed by MTA application. The specimens were then subjected to glucose leakage analysis at 48 h, 7 days, and 14 days. One-way ANOVA test was used for raw data and Chi-square test for consolidated data to test the significance of difference between the variables. SPSS software version 20 was used for analyzing the data. Results: Group 1 showed significantly more leakage than Group 2 and Group 3 at all time intervals, whereas Group 3 showed the least microleakage at 48 h, 7 days, and 14 days. Conclusion: MTA had a better sealing ability when root-end cavities were conditioned with 5% citric acid followed by diode laser irradiation.